Analysis of the Use of Close Friend Feature on Instagram as a Social Networking Site Using Communication Privacy Management Theory - Sakinah, Sofa (Persatuan Wartawan Indonesia, 2021)
The development of digital media technology gave rise to social media, especially Instagram which is a site used to exchange information and fulfill social communication needs in various circles. This study specifically analyzes the use of the Close Friend feature found on Instagram social media which is used for various objectives of each user. The research method uses descriptive quantitative content analysis through text analysis from various previous studies related to the use of the Instagram feature. One study showed that the effectiveness of the Instagram feature in increasing adolescent friendships in the digital era was dominant in the Close Friends feature as much as 61.2%. Close friends feature (close friend) was promoted because of the self-disclosure factor, as well as the convenience of users in uploading Instagram stories. The level of openness to the high categorydue to the proximity selecting and content sharing on this feature. The close friends feature is considered more private for Instagram users because they are free to choose their audience and upload based on their needs and desires. It was also mentioned how users manage their privacy when using the Instastory feature on Instagram social media where the privacy management is based on the Communication Privacy Management (CPM) criteria or Communication Privacy Management and is seen in the usage strategy when using the Insta Story feature on Instagram. Informants tend to have different reasons behind their decision to reset their privacy when using their social media.